Place of the method of crime in the sphere of economic activity in the system of criminalistics description - Дудніков, А. Л. (Theory and practice of jurisprudence, 2016)
The criminalistics features of methods of crimes in the sphere of economic activity are analyzed, the concept of criminalistics description of crimes is investigated, the structure of criminalistics description of crimes in the sphere of economic activity is offered and the location of method in its system is determined.